A review for selecting medicinal plants commonly used for malaria in Uganda - Ajayi, Clement O.; Elujoba, Anthony A.; Kasali, Félicien M.; Tenywa, Mercy G.; Okella, Hedmon; Weisheit, Anke; Tolo, Casim U.; Ogwang, Patrick E. (African Journal of Pharmacy and Pharmacology, 2020)
The menace of current cases of parasite resistance to antimalarial drugs, non- availability and accessibility, and the high costs of pharmaceutical products contribute to the high rate of medicinal plants consumption in the treatment of malaria in Uganda. Different ethnobotanical surveys on medicinal plants with antimalarial properties have been conducted across different geographical regions in Uganda in order to identify and select the most commonly used antimalarial plants as candidates in the proposed national herbal pharmacopoeia. The available literature on the medicinal plants used against malaria in the western, central, eastern and northern geographical regions in Uganda was selected from reputable journals using various citation databases as guides. The commonly used antimalarial plants in the regions were searched using relevant journals on previously established ethno-botanical survey. They were then ranked in order of percentage frequency of appearance in the literature from surveys across the country. Fifteen medicinal plants were selected in this way from several antimalarial plants cited. Vernonia amygdalina and Azadirachta indica appeared most (100%), followed by Carica papaya, Mangifera indica and Hoslundia opposita with 80% appearance each across the 4 regions.The medicinal plants from this review were therefore ranked as the most used for treatment of malaria in Uganda and therefore, could be recommended for herbal pharmacopoeial standards development.
Keywords: Antimalarial; Medicinal plants; Antiplasmodial; Herbal pharmacopoeial standards